The Role of Family Background of Speaking Skill: A Comparison between Public and Private School Students - Santoso, Nanda Kristia; Jamilah, Jamilah; Ciptaningrum, Dyah Setyowati; Friassantano, Risgar; Lidya, Marina (LPPM Institut Pendidikan Nusantara Global, 2025)
This study compared eighth-grade students from Tanjungpinang's SMPN 7 (a public school) and SMP Muhammadiyah (a private school) during the 2024–2025 school year in order to examine the impact of family background on students' English-speaking abilities. 60 students' responses to structured questionnaires and speaking assessments were gathered using a quantitative comparative design. A rubric measuring fluency, accuracy, pronunciation, vocabulary, and coherence was used to evaluate speaking performance, and questionnaires examined parental education, income, home language environment, and English learning support. Students attending private schools typically came from families with higher socioeconomic status and educational attainment, according to descriptive statistics. With notable improvements in pronunciation and fluency, these students also performed better in speaking than their peers in public schools. Speaking scores for the two groups differed significantly, according to inferential analysis using an independent sample t-test. Additionally, correlation analysis showed that students' speaking abilities and family background factors specifically, parental education and the frequency of English use at home were positively correlated. The results showed that students' oral English proficiency was significantly shaped by their family background, and that this influence was stronger for students attending public schools with fewer institutional resources. In order to promote equitable language learning opportunities, the study emphasized the combined effects of the home and school environments on language development and the necessity of cooperation between educators, parents, and legislators.